Enhancing perceived employability: An interactionist perspective on responsibilities of organizations and employees. Issue 6 (7th September 2015) - Veld, Monique; Semeijn, Judith; Vuuren, Tinka van
Abstract : Purpose: – The purpose of this paper is to investigate the moderating role of employees' willingness to invest in training and development and willingness for mobility on the relationship between human resource (HR) management practices and employability. As such, the study takes an interactionist perspective, building on human capital theory and social exchange theory. Investigating possible interaction effects is highly relevant as little is known yet on how organizational efforts (i.e. policies and activities) and individual effort of employees might strengthen each other in their aim of enhancing employability. Design/methodology/approach: – Analyses were based on a sample of 1, 346 respondents from 91 primary school locations in the Netherlands. Hypotheses were tested using regression analyses controlling for nesting of the data. Findings: – The results indicate that HR activities and employees' willingness are positively related to employability. Furthermore, only employees' willingness for mobility strengthens this relationship, not their willingness for training and development. These results indicate that both organizations and employees are responsible for enhancing employability. Practical implications: – Both HR activities and employee willingness appear to play a significant and interactive role for enhancing employability. Therefore, explicit cooperation between employee and organization in light of optimizing employability seems warranted. Originality/value: – This study extends current research on enhancing employability, by theorizing and testing the combined efforts of organizations and employees from an interactionist perspective.